Interculturality and (Post)colonialism: Ethnicity, Nationalism, Cultural Memory and Identity ; Innsbruck University Austria (2-6 December 2008) Symposium Interculturality and (Post)colonialism: Racism, Slavery and Literature - Gjurgjan, Ljiljana Ina (2008)
In this paper the American and Irish construction of national identity. are analyzed. In this paper I want to analyze the American and Irish construction of national identity. In the case of America the lack of unifying national myths and heroes (such as Cuchulain in the Irish tradition) are substituted by the symbols of the American identity such as the statue of liberty, American dream and the American flag. These symbols, I want to argue, are the most prominent landmarks of the American national identity, overcoming ethnic and other differences. Though in American cultural history national and nationalistic usually refers to ethnic movements, such as the Black movement in the 60s, the black and the white nationalisms being seen as contesting ones, it is still possible to talk about the American sense of national identity. It is however constructed differently then the European sense of identity which relies on the national language and collective national myths as their anchors. In particular, they are indispensable in the construction and preservation of national identity in the stateless nations.